The Relationship Between Physical Activity, Stress And Sleep Duration With Hypertension In Senior High School Adolescents In Palembang City - Aisyah, Siti; Kurnianto, Andra; Nita, Sri (Jurnal Health Sains, 2025)
Hypertension in adolescents is an emerging public health concern, with its prevalence in Indonesia increasing from 3.11%–4.6% in 2005 to 8.3% in 2008, and it is predicted to continue rising annually. Adolescent hypertension often goes undetected, leading to severe health complications in adulthood if left uncontrolled and untreated. Several lifestyle factors, including physical activity, stress levels, and sleep duration, have been identified as potential contributors to the incidence of hypertension in adolescents. This study aims to analyze the relationship between physical activity, stress, and sleep duration with the incidence of hypertension among high school students in Palembang City.This research adopts an analytical cross-sectional study design, with a total sample of 467 high school students selected based on inclusion and exclusion criteria. Data were analyzed using the Chi-Square statistical test to determine associations between variables. The results indicate a significant relationship between physical activity and hypertension (p = 0.008), as well as between stress and hypertension (p = 0.005). However, no significant relationship was found between sleep duration and hypertension (p = 0.054) These findings suggest that low physical activity and high-stress levels contribute to hypertension in adolescents, emphasizing the need for preventive strategies such as promoting regular physical exercise and stress management programs in schools. Future research should explore longitudinal studies to assess the long-term effects of adolescent hypertension, intervention-based research to determine the effectiveness of physical activity programs, and the potential role of sleep quality rather than duration in blood pressure regulation. This study highlights the importance of early lifestyle modifications to prevent hypertension-related complications in adulthood.